HUBUNGAN PENGETAHUAN, SIKAP, DAN MEDIA MASSA TERHADAP KECEMASAN MASYARAKAT PADA MASA PANDEMI COVID-19 DI KECAMATAN MAWASANGKA TAHUN 2021 - Fika Mustika Tanaka; Hariati Lestari; Jusniar Rusli Afa (Endemis Journal, 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (Sars – Cov 2) which is a new type of coronavirus that was discovered in 2019. Until now, Covid-19 has had an impact on changing aspects of people's lives. including the emergence of anxiety. The knowledge gained can only affect anxiety. Attitudes can affect the anxiety of the community itself. Mass media can also affect anxiety because there is a lot of information from the media that is not necessarily true. The purpose of this study was to determine the relationship between knowledge, attitudes and mass media on public anxiety during the Covid-19 pandemic in Mawasangka District in 2021. The method in this study used a cross sectional approach. The population in this study was the entire community in Mawasangka District as many as 29,131 people. The sample in this study amounted to 379 people. Sampling was done by proportional stratified random sampling technique. The data was collected using a questionnaire that was filled in via a google form and some of it was distributed manually. Statistical test using chi square test. The results of this study indicate that there is no relationship between knowledge and anxiety (p Value = 0.376 > 0.05), there is a relationship between attitude and anxiety (p Value = 0.027 < 0.05) and there is no relationship between mass media and anxiety (p Value = 0.107 > 0.05). The conclusion is that there is no relationship between knowledge and anxiety, there is a relationship between attitude and anxiety, and there is no relationship between mass media and anxiety.